A Neuroanatomy of Positive Affect Display – Subcortical Fiber Pathways Relevant for Initiation and Modulation of Smiling and Laughing - Coenen, Volker A.; Sajonz, Bastian E. A.; Hurwitz, Trevor A.; Böck, Marlies; Hosp, Jonas A.; Reinacher, Peter C.; Urbach, Horst; Blazhenets, Ganna; Meyer, Philipp T.; Reisert, Marco (Frontiers in Behavioral Neuroscience, 2022)
Background: We here report two cases of stimulation induced pathological laughter under thalamic deep brain stimulation for essential tremor and interpret the effects based on a modified neuroanatomy of positive affect display (PAD). Objective/Hypothesis: The hitherto existing neuroanatomy of PAD can be augmented with recently described parts of the motor medial forebrain bundle (motorMFB). We speculate that a co-stimulation of parts of this fiber structure might lead to a non-volitional modulation of PAD resulting in pathological laughter. Methods: We describe the clinical and individual imaging workup and combine the interpretation with normative DTI-tractography descriptions of motor connections of the ventral tegmental area (n=200 subjects, HCP cohort), (18FDG) PET and volume of activated tissue simulations. We integrate these results with literature concerning PAD and the neuroanatomy of smiling and laughing. Results: DBS electrodes bilaterally co-localized with the MB-pathway (“limiter pathway”). The FDG PET activation pattern allowed to explain pathological PAD. A conceptual revised neuroanatomy of PAD is described. Conclusion: Eliciting pathological PAD through chronic thalamic DBS is a new finding and has previously not been reported. PAD is evolution driven, hard wired to the brain and realized over previously described branches of the motorMFB. A major relay region is the ventral tegmental area/mammillary body complex. PAD physiologically undergoes conscious modulation mainly via the MB branch of the motorMFB (limiter). This limiter in our cases is bilaterally disturbed through DBS. The here described anatomy adds to a previously described framework of neuroanatomy of laughter and humor.